Lean Product Development Implementation Approach: Empirical Evidence from Indian Lean Manufacturers - Biazzo, Stefano; Panizzolo, Roberto; Gore, Amol (International Journal of Industrial Engineering and Management, 2017)
This paper investigates the application of Lean concepts in innovation processes of a group of Indian firms which have undertaken a significant path of lean transformation both in the factory and in product development. The paper first develops an assessing framework for evaluating the Lean Product Development (LPD) transformation initiatives adopted by firms. This framework, which has been developed on the base of literature review and reviewed through a Delphy study, is subsequently used to analyse 18 Indian manufacturing companies which have embarked in LPD initiatives. The obtained empirical results contrast with the theory-based requirements of a balanced approach between process and product focus. Most of the studied companies have implemented the process-focused LPD initiatives that aim at improving the overall performance of the development process by making it more fluid and efficient through the operationalization of flow and pull principles. Lower adoption is in place for product-focused initiatives that evoke the lean principle of value and the search for effectiveness in responding to customer needs. Only a small number of firms have followed a fully integrated approach that means the adoption of a significant number of initiatives in both product and process domains. We think that the allocation of LPD transformation initiatives into proposed categories can help managers prioritize investment decisions about lean transformation in product development processes. Article history: Received (27.02.2017); Revised (15.06.2017); Accepted (09.08.2017)